Association of SNP Marker in the IGF1 Gene with Carcass Traits in Crossbred Cattle among Thai Native, Brahman and Charolais - Jeanmas, Arraya; Sopannarath, Panwadee; Tumwasorn, Sornthep; Loongyai, Wiriya (Agriculture and Natural Resources, 2014)
The objectives of this study were to estimate the allele and genotype frequencies of insulin-like growth factor 1 (IGF1) polymorphisms as well as to assess the association between these polymorphisms and carcass traits in crossbred cattle among Thai Native, Brahman and Charolais (n = 238). A single nucleotide polymorphism (SNP) of the IGF1 gene (c.512C < T) was determined by polymerase chain reaction-restriction fragment length polymorphism assay using the SnaBI restriction enzyme. The results showed that the frequency of the B allele was higher than that of the A allele (0.82 and 0.18, respectively). The IGF1 genotype and average effect of allele substitution were not associated with hot and cold carcass weights, rib eye area, backfat thickness, marbling score and dressing percentage (P > 0.05). The SNP of the IGF1 gene was not associated with carcass traits. Therefore the SNP of the IGF1 gene could not be used as a marker for improving carcass traits in this crossbred cattle population.